The Mirroring Phenomenon in Cultural Consciousness of Russia - Osmukhina, Olga Yurievna (Journal of History Culture and Art Research, 2019)
The article considers the understanding of the phenomenon of mirroring. In particular, the specifics of the mirroring phenomenon interpretation in scientific studies is analyzed with the help of the comparative historical method and the integral method of literary work analysis. Mirroring is considered as a philosophical and aesthetic phenomenon, as well as a category of modern cultural studies, semiotics and literary studies. The paper in question follows the history of mirror not as a materialistic object, but rather as the phenomenon which meaning goes beyond “physical” nature; it is traced what meanings mirroring acquires in different epochs in the European and Russian culture – from ancient times (the folklore understanding of a mirror as a boundary between worlds) to modern interpretations. It is mentioned in the work that the mirror was not only a common household item, but also a symbolic object that accompanies an individual’s search for himself in the process of self-understanding since one’s own reflection can reveal similarities or differences, kinship or alienity within oneself. The article examines the interpretation of the phenomenon of mirroring in the humanitarian thought of the twentieth century, primarily in the research of M. M. Bakhtin. The entire corpus of the most important scientific works of M. M. Bakhtin has been analyzed: “Author and hero in aesthetic activity”, “Man at the mirror”, “Problems of Dostoevsky’s creativity”, “Problems of Dostoevsky’s poetics” etc. It is found that the phenomenon of mirroring in the works of M. M. Bakhtin is directly associated with the categories of the “other”, “out-of-search”, “double”, which are dominant in the dialogical concept of the scientist (the other as an “I-twin” turns “others” into objects of his own vision with the help of the mirror). The mirror appears as the object of a character’s identification with his own reflection, himself, and is connected with the conception of “strange consciousness” as a means of “internal” self-equality on looking at yourself with “other’s” eyes.